دراسة لبعض الحالات المصابة بالهشاشة العظمية والتي تم تشخيصها بواسطة جهاز SONOST-2000 في مستشفى العظام-مصراتة (Journal of Academic Research, 2024)
In this paper, we were studied(61) cases  that visited Al-Jazeera Orthopedic Hospital in Misurata during the period from the beginning of April 2021 to the end of December 2021. The ages of the patients ranged from 20 years to 80 years and above, and the percentage of women affected was higher than men.In fact, several diseases affect bones, the most famous of which is (osteoporosis). Normal, healthy bone resembles a piece of sponge filled with small gaps and pores, while the bone affected by osteoporosis has fewer gaps and its size expands, and the bones become necrotic, thus becoming more fragile and losing their hardness and breaking very easily when exposed to the slightest shock, which does not happen in normal human conditions and its recent spread and its general increase among women and men and its association with women more. In fact, the SONOST-2000 device examination was one of the basic examinations that showed the presence of some cases of osteoporosis.Osteoporosis was also defined in terms of its types, symptoms, and the most important factors that contribute to its occurrence, as well as methods of diagnosing and treating it. This information is important in spreading health awareness and educating the general public in order to take precautions and be careful of this disease.